PERBEDAAN RISIKO INVESTASI SAHAM PERUSAHAAN DAN ANALISIS SEBELUM DAN SESUDAH MELAKUKAN AKUISISI - Utami, Hayu Yolanda (Jurnal Pelangi : Research of Education and Development, 2015)
This aim of the research is to analyze the different stock investment risk before and after make acquisition process. The research take 10 company for samples and have 60 days before and 60 days after acquisitions process. The research using the model of beta coefficient (β) and t-test paired sample test. The result of the research showed have the different stock investment risk before and after acquisition process with stock investment risk before acquisitions more than after acquisitions process.